Divergierende Wohnungsmärkte in Deutschland - Guido Spars; Michael Voigtländer (Wirtschaftsdienst, 2015)
Großstädte und viele Universitätsstädte wachsen, während andere Städte schrumpfen. Dies stellt insbesondere den Wohnungsmarkt vor große Herausforderungen, da in einigen Städten neuer Wohnungsbau dringend erforderlich ist und andere Städte mit zunehmendem Leerstand umgehen müssen. Die Autoren zeigen die Folgen für die Wohnungsmärkte in Deutschland anhand des Beispiels Wuppertal, Köln und Düsseldorf auf und stellen Lösungsansätze vor. – – Due to demographic changes, housing markets in Germany differentiate notably. Frequently, shrinking and booming cities are located closely to each other, as in the cases of Wuppertal, Cologne and Dusseldorf. In order to enhance economic efficiency and prevent the demolition of buildings in some cities and the simultaneous erection of new houses and infrastructure in others, it would be favourable to implement incentives using the living space in shrinking cities. Better transportation facilities, more leisure time facilities and moderate financial incentives could make shrinking cities like Wuppertal more attractive, thereby encouraging price sensitive households to stay or migrate there.
Keywords: H7; R3; 330; Wohnungsmarkt; Räumliche Verteilung; Wohnungsbau; Deutschland